Transformasi Sematan Klausa Relatif pada Teks Terjemahan Surat Al-Mulk - Ach. Fahmi Alwan; Imam Asrori (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Studies on relative clause embedded transformation sentences have been conducted extensively, but are still limited and have not paid attention to religious texts such as the translated text of the Qur'an. This study aims to analyze (1) the form of embedded transformation sentences, (2) the process of embedded transformation sentences, and (3) the rules of embedded transformation sentences found in the translated text of Surah Al-Mulk. The data used in this study are verses from Surah Al-Mulk that have a relative clause embedded transformation sentence pattern. The data collection method in this study uses documentation techniques, listening techniques, and note-taking techniques. The data obtained were analyzed using intralingual and extralingual matching methods. The results of this study found that there are 3 forms of relative clause embedded transformation sentences, namely the Embedded-Dense (S-R) form which consists of 6 verses, the Closed-Embedded form which consists of 2 verses, and the Embedded-Dense-Embedded (S-R-S) form which consists of 2 verses. Based on the position of the embedding, at the beginning of the sentence there is a sentence pattern of Embedded-Dense (S-R) and at the end of the sentence there is a Close-Embedded (R-S). Based on the rules of sentence transformation, there is a pattern of Embedded-Dense-Embedded (S-R-S) in complex sentences and a pattern of Embedded-Dense (S-R) in simple sentences.